Find the value of -
3 5 1 1 − 2 4 4 2 0 4 8 + 3 8 1 − 4 5 3 7 8 9 2 − 2 1 1 2 0 + 5 6 2 6 2 1 4 4 − 1 9 6 6 0 8 + 6 1 4 4 0 ⋯
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Could you please increase the font? The radicals cannot be read. Nevertheless, Nice solution to a good question. Upvoted!
Log in to reply
Thank You so much! Support of people like you makes me post problems and there solutions :)
Good question but there is a trick to bypass the algorithm. One can guess the answer easily as 7 is the only whole no. cube root possible after subtracting multiples of 24 from 511 ;)
Yes. That was my approach. Answer< 5 1 1 3 1 . 8 3 = 5 1 2 . S o a n s w e r = 7 .
Problem Loading...
Note Loading...
Set Loading...
Let f ( x ) be x − 1
f ( x ) = 3 ( x − 1 ) 3
f ( x ) = 3 x 3 − 1 − 3 x ( x − 1 )
f ( x ) = 3 x 3 − 1 − 3 x 4 ( x − 1 ) 4
f ( x ) = 3 x 3 − 1 − 3 x 4 x 4 − 4 x 3 + 6 x 2 − 4 x + 1
f ( x ) = 3 x 3 − 1 − 3 x 4 x 4 − 4 x 3 + 6 x 2 − 4 x + 4 − 3
f ( x ) = 3 x 3 − 1 − 3 x 4 x 4 − 4 x 3 + 6 x 2 − 3 − 4 ( x − 1 ) )
f ( x ) = 3 x 3 − 1 − 3 x 4 x 4 − 4 x 3 + 6 x 2 − 3 − 4 5 ( x − 1 ) 5
f ( x ) = 3 x 3 − 1 − 3 x 4 x 4 − 4 x 3 + 6 x 2 − 3 − 4 5 x 5 − 5 x 4 + 1 0 x 3 − 1 0 x 2 + 5 x − 1
f ( x ) = 3 x 3 − 1 − 3 x 4 x 4 − 4 x 3 + 6 x 2 − 3 − 4 5 x 5 − 5 x 4 + 1 0 x 3 − 1 0 x 2 + 4 + 5 x − 5
f ( x ) = 3 x 3 − 1 − 3 x 4 x 4 − 4 x 3 + 6 x 2 − 3 − 4 5 x 5 − 5 x 4 + 1 0 x 3 − 1 0 x 2 + 4 + 5 6 ( x − 1 ) 6
f ( x ) = 3 x 3 − 1 − 3 x 4 x 4 − 4 x 3 + 6 x 2 − 3 − 4 5 x 5 − 5 x 4 + 1 0 x 3 − 1 0 x 2 + 4 + 5 6 x 6 − 6 x 5 + 1 5 x 4 . . .
Plugging in x = 8 , we get-
f ( 8 ) = 3 5 1 2 − 1 − 2 4 4 4 0 9 6 − 2 0 4 8 + 3 8 4 − 3 − 4 5 3 2 7 6 8 5 − 2 0 4 8 0 + 5 1 2 0 − 6 4 0 + 4 + 5 6 2 6 2 1 4 4 − 1 9 6 6 0 8 + 6 1 4 4 0 . . .
f ( 8 ) = 3 5 1 1 − 2 4 4 2 0 4 8 + 3 8 1 − 4 5 3 7 8 9 2 − 2 1 1 2 0 + 5 6 2 6 2 1 4 4 − 1 9 6 6 0 8 + 6 1 4 4 0 . . .
⇒ f ( 8 ) = 8 − 1
7